Naturalisierung im deutsch-jüdischen Spannungsfeld - Avraham Rot (Recherches Germaniques)
The article reconstructs Gottfried Benn’s reception of Benedictus de Spinoza in his essay Goethe und die Naturwissenschaften, published in the Neue Rundschau in 1932. While Spinoza’s philosophy is fundamentally at odds with the conception of art as irrational, acausal, and transcendent, an idea running through all of Benn’s works, Benn nevertheless positively invoked the Romantic neo-Spinozist concept of nature ‘hen kai pan’ (One and All) and praised Goethe as a Spinozist natural scientist, one who had endorsed Spinoza’s doctrine of monism while adding “nuance”. This can be read as a gesture towards contemporary German-Jewish admirers of Spinoza, especially towards Rudolf Kayser, the editor of the Neue Rundschau between 1922-1933, whose relationship to Benn is considered here in light of new archival findings, but also of the debate on the new physics and mathematics, which served in the German-Jewish tension field as a space for the articulation of questions of nationality, religion and anti-Semitism. However, this “monism”, which was appropriated in Benn’s writings between 1932-1933 through Goethe, also enabled the transition from a concept of universal metaphysical unity to the political-aesthetic celebration of the National Socialist “total” state.